HereSay: Gamifying Urban Crowdsourcing Through Affordance-Based Data Collection - Baer, Manuel F.; Fonseca Alves, Luma; Laato, Samuli (United States, 2026)
We present HereSay, a gamified mobile crowdsourcing application that transforms urban observation into engaging gameplay whilst collecting valuable data for participatory planning. The app addresses the challenge of sustaining citizen engagement in urban planning through five integrated gamification mechanics: progressive unlocking, daily streaks, experience points, levels and leaderboards. Unlike traditional planning tools that solely rely on functional categorisation, HereSay adds affordance-based prompts to capture how citizens actually perceive and use urban spaces, with particular emphasis on urban landscape perception. Built using Flutter and Firebase for cross-platform accessibility, the application requires only standard smartphone capabilities. Initial evaluation with seven users demonstrates strong engagement with gamification features and successful motivation to explore urban spaces. The application showcases a scalable solution for inclusive citizen participation that bridges the gap between informal experiential knowledge and structured planning data.
GamiFIN '26 : Proceedings of the 10th Annual International GamiFIN Conference 2026